Sensemaking Under Pressure: The Influence of Professional Roles and Social Accountability on the Creation of Sense - Cornelissen, Joep P. (Organization Science, 2012)
In this paper, I elaborate a theoretical model of how individuals come to make or create sense through their language while being accountable to others. Using accounts of corporate communication professionals who made sense of anomalous circumstances, I analyze how they used metaphorical words and expressions to organize their accounts and to negotiate between their own individual commitments and perceived social expectations. Based on the analysis, I induce that professionals (a) use individual metaphors to align themselves with the expectations of others and to mark particular roles for themselves that strictly meet those expectations (“strategic shifting”) when they perceive the social approval motive as strong; (b) engage in the extended use of a single metaphor to compress a situation into a frame that mediates between individual convictions and others' expectations (“framing”) when they know the views of others but are also strongly motivated to think through a circumstance as part of their professional role or previous commitments; and (c) systematically use a combination of metaphors that are blended and elaborated into a plausible narrative that attributes responsibility and prescribes a course of action (“narration”) when they are in a position (as part of their role) to define a circumstance, are unconstrained by past experiences, and do not directly know the views of others. This model integrates findings from prior research and combines the influence of role-related commitments and social accountability pressures on sensemaking.